DATA PENYAKIT KOKSIDIOSIS TAHUN 2011 - 2013 DI BALAI BESAR VETERINER (BBVet)WATES YOGYAKARTA - , SUMBODO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The practice of field work Diploma III Veterinary Programs Gadjah Mada University of Yogyakarta in 2014 was held in Balai Besar Veterinary (BBVet) Wates. Balai Besar Veterinary Wates is a technical executive unit which is under and responsible to the Community Development Directorate General of livestock production and veterinary is in charge of carrying out the probe, veterinary testing, development of techniques, methods of investigation and testing of veterinary. The practice of field work was held on 21-25 April 2014 in Epidemiology and Parasitology Laboratory, with the aim of knowing the list instances of disease caused by protozoa of the genus Eimeria as a cause of koksidiosis disease from 2011 to 2013. The activities included are knowing genesis koksidiosis, the number of incoming submissions, samples that contain positive oosista koksidia and find out the test were used. Based on the list from koksidiosis cases in 2011-2013 at the Balai Besar Veterinary Wates Yogyakarta, the total shipment of samples from areas of services such as special region of Yogyakarta, Central Java and East Java as well as other regions such as West Java and Sumatra, the positive portion of the sample contains oosista koksidia with the percentage of incident cases in 2011 amounting to 40,09%, 2012 of 32,91% and 2013 of 28,99% contained on dogs, rabbit, sheep/goat, cow/buffalo and cats are caused by the genus Eimeria spp. Trials conducted to know the parasites is a floating test with withlock method to find and calculate egg/oosista Protozoan that floats in the room count Whitlock. Overall observations from list observed show that young animals are animals that are susceptible to koksidiosis and the most vulnerable regions stricken with koksidiosis is an area of the island of Sumatra with the percentage incidence of 66,67%.